(untitled) (Research, Society and Development, 2020)
Objective: To describe the epidemiological profile of tuberculosis in persons deprived of their liberty in Brazil. Methodology: Epidemiological and cross-sectional study based on notified cases of tuberculosis between 2010 and 2019, based on SINAN databases. Results and discussion: 57,486 cases of tuberculosis were reported in Brazil, in a population deprived of liberty. Noteworthy is the increase in the number of TB cases between 2010 and 2019. It was identified that the population deprived of liberty with the highest rate of TB is male, between 20 and 39 years of age, claiming to be brown and black with elementary school. incomplete and does not receive government benefit. The absolute number of people who are diagnosed and notified with Tuberculosis and who live with Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome are 4,107 and 3117, respectively. Conclusion: There was a high growth in the number of confirmed cases of Tuberculosis in people deprived of their liberty. The study identified the characteristics of the disease within private prison, as well as demonstrated the magnitude of TB in relation to the total number of reported cases.